1995
DOI: 10.1002/sia.740231304
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a single chemical functional group to a polymer surface with a mass‐separated low‐energy ion beam

Abstract: A mass-separated low-energy ion beam system was used to deliver pure O H + and N H + to 15 nm thick polystyrene films on silicon in ultrahigh vacuum. This was done in an effort to produce specific surface chemical functional groups. X-ray photoelectron spectroscopy showed that when the bombardment energy of OH+ exceeded 10 eV, or the dose was higher than 1 x 10l6 ions ern-', a mixture of C-OH, C-C=O and C-COOH groups was produced, along with severe damage to the aromatic rings. However, for bombardment at 10 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…A small electron current from the filaments of a sputter ion gun was delivered to the target surface during ion exposure to compensate for ion beam induced charging. 11 Control exposures found negligible contributions to PS modification from the background gas and the neutralizing electron beam.…”
Section: Methodsmentioning
confidence: 97%
“…A small electron current from the filaments of a sputter ion gun was delivered to the target surface during ion exposure to compensate for ion beam induced charging. 11 Control exposures found negligible contributions to PS modification from the background gas and the neutralizing electron beam.…”
Section: Methodsmentioning
confidence: 97%
“…A few studies have demonstrated that low energy ion beams can be used to selectively modify surfaces. 23,25,203,311,312 However, most stud-ies employ chemically nonspecific modifications to alter the adsorbate. [313][314][315] Chemically selective incorporation of functional groups into surfaces using reactive gaseous ions has been achieved.…”
Section: Surface Modification By Ionõsurface Reactionsmentioning
confidence: 99%
“…Mass separated low energy polyatomic ion beams have several advantages for practical surface modification due to the highly surface-selective nature of the polyatomic-surface interaction, the unique collision dynamics, and the ability to transfer intact chemical functionality to the surface. [1][2][3] Low and medium energy atomic ions have been used in microelectronics manufacturing for repairing photolithography masks, doping, producing interconnect features, and submicron lithography. 4,5 Atomic ions have also been used to grow hard inorganic films 6 and selectively modify polymer films.…”
Section: A Polyatomic Ion-surface Modificationmentioning
confidence: 99%